2015
DOI: 10.1371/journal.pone.0125818
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Prognosis of Coagulase-Negative Staphylococcal Endocarditis: Impact of Vancomycin Minimum Inhibitory Concentration

Abstract: This study describes coagulase-negative staphylococcal (CoNS) infective endocarditis (IE) epidemiology at our institution, the antibiotic susceptibility profile, and the influence of vancomycin minimum inhibitory concentration (MIC) on patient outcomes. One hundred and three adults with definite IE admitted to an 850-bed tertiary care hospital in Barcelona from 1995-2008 were prospectively included in the cohort. We observed that CoNS IE was an important cause of community-acquired and healthcare-associated IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The importance of vancomycin susceptibility in methicillin-resistant and even methicillin-susceptible strains is controversial. After initial studies described worse outcomes for methicillin-resistant strains with high vancomycin MIC values [9,30], various metaanalyses on the relevance of MIC in SA infections have associated values ≥2 μg/mL with higher mortality (OR 1.72; 95% CI: 1.34-2.21) and values ≥1.5 μg/mL with [31] and even in IE [32] and bacteremia due to MSSA with MIC ≥1.5 μg/ mL, which was associated with a higher risk of complicated bacteremia [33,34]. In contrast, a longitudinal, prospective, multicenter study of MRSA endocarditis found no association of vancomycin MIC ≥1.5 μg/mL with higher mortality, although it was related to a greater persistence of bacteremia and a higher frequency of sepsis/septic shock, peripheral embolism, and arthritis/osteomyelitis [35].…”
Section: Discussionmentioning
confidence: 99%
“…The importance of vancomycin susceptibility in methicillin-resistant and even methicillin-susceptible strains is controversial. After initial studies described worse outcomes for methicillin-resistant strains with high vancomycin MIC values [9,30], various metaanalyses on the relevance of MIC in SA infections have associated values ≥2 μg/mL with higher mortality (OR 1.72; 95% CI: 1.34-2.21) and values ≥1.5 μg/mL with [31] and even in IE [32] and bacteremia due to MSSA with MIC ≥1.5 μg/ mL, which was associated with a higher risk of complicated bacteremia [33,34]. In contrast, a longitudinal, prospective, multicenter study of MRSA endocarditis found no association of vancomycin MIC ≥1.5 μg/mL with higher mortality, although it was related to a greater persistence of bacteremia and a higher frequency of sepsis/septic shock, peripheral embolism, and arthritis/osteomyelitis [35].…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis has different virulence factors such as cysteine protease, serine protease, lipase, metalloprotease with elastase activity, resistance to antibiotics, ability to produce delta toxin and ability to adhere to and form biofilm on the surface of foreign bodies such as implanted devices [ 69 , 70 ]. The ability to form biofilm on the surface of foreign bodies leads to the emergence of antibiotic-resistant S. epidermidis isolates, and the infections induced by these organisms have become increasingly difficult to eradicate.…”
Section: Cons In Meningitismentioning
confidence: 99%
“…In recent years, an increase in the frequency of bacteremia and endocarditis caused by CNSA has been reported, including native valve endocarditis (22). Maria et al (23) reported that the prevalence of CNSA-related IE was 16% and the frequency of native valve endocarditis was 35% in their adult studies, which included 13 years of data. In our study, CNSA was the most frequent IE agent with five cases (45.5%), where three patients had native valves and two had condiut valves.…”
Section: Discussionmentioning
confidence: 99%